A Csound opcode for a triode stage of a vacuum tube amplifier - Fink, Marco; Rabenstein, Rudolf (14th International Conference on Digital Audio Effects, DAFx 2011, 2011)
The Csound audio programming language adheres to the inputoutput paradigm and provides a large number of specialized commands (called opcodes) for processing output signals from input signals. Therefore it is not directly suitable for component modeling of analog circuitry. This contribution describes an attempt to virtual analog modeling and presents a Csound opcode for a triode stage of a vacuum tube amplifier. Externally it communicates with other opcodes via input and output signals at the sample rate. Internally it uses an established wave digital filter model of a standard triode. The opcode is available as library modul
Keywords: Analog circuitry; Analog modeling; Component modeling; Input and outputs; Input-output; Library modules; Opcodes; Output signal; Sample rate; Vacuum-tube amplifiers; Wave digital filters; Amplifiers (electronic); Digital filters; Tubes (components); Vacuum; Triodes